On the Relevance of Education Research From a Non-Affirmative Perspective: A Constructive Critique - Andreas Nordin; Bettina Vogt (Nordisk tidsskrift for pedagogikk og kritikk)
This article argues for the problematic dominance of education research striving for relevance for policy and practice, with little to no consideration of its contribution to shared internal disciplinary discourse. Drawing on non-affirmative education theory, we use empirical examples from the Swedish context to contend that such a one-sided focus on external relevance may lead to a relevance paradox in which education research becomes increasingly irrelevant while striving for relevance. Two issues are discussed in relation to this development. First, such a discourse on education research runs the risk of becoming undisciplined in the sense that it becomes detached from the shared disciplinary language, with little to no connection to fundamental education theory. Second, education research runs the risk of becoming uncritical. In closing the gap between practice/policy and research, education researchers jeopardise their critical distance and become subordinated to practitioners and policymakers in an unequal and uncritical relationship. Finally, we argue for a more dynamic and reflexive understanding of the relevance of education research, where the reflexive relationship between policy/practice and fundamental education theory research is understood as the thing that makes it possible for disciplinary discourse to thrive.